Evaluation Of Antioxidant Properties Of Different Parts Of Amorphophallus Commutatus, An Endemic Aroid Of Western Ghats, South India - R. KAVITHA KRISHNA,; S.KRISHNAKUMARI,; S.CHANDRAKALA, (International Journal of Pharma and Bio Sciences, 2012)
Amorphophallus commutatus ( Araceae) a rare cormous herb endemic to western ghats has been used by the tribes of sitamata wild life sanctuary, Rajasthan, India and tribes living in the Western Ghats, India for various ailments. The current study was carried out with an objective to investigate the enzymatic and non enzymatic contents of the tuber and leaves of the plant adopting eight enzymatic methods (Superoxide dismutase, Catalase, Guaicol peroxidase,Ascorbic acid oxidase, Glutathione peroxidase, Glutathione reductase, glucose – 6- phosphate dehydrogenase and polyphenol oxidase) and three non enzymatic methods (Phenol, Ascorbic acid, Glutathine reduced). The tuber exhibited significant SOD (47.7±5.5 U/g tissue), AAO(0.38±0.12U/g tissue), PPO(0.8±0.45U/g tissue), Ascorbic acid (1.6±0.5mg/g tissue) and total phenol(0.2±0.22mg/g tissue). Young leaves contained significant CAT(64.3 ±6.02 U/g tissue), GR (1.3±0.7 U/g tissue) and Glutathione (6.21 ±0.6 mg/g tissue) content. The mature leaf exhibited significant G6PD activity (9.97±2.0 U/g tissue). Our results reveal the innate antioxidant potential of Amorphophallus commutatus and therefore can be utilised for supplementing the antioxidant needs in the diet.